Arquivo Central da UFPA: uma experiência extensionista em difusão arquivística - ARAÚJO, Izabela Carolaine da Silva (2023)
This research aimed to present the experience of disseminating the collections of the Central Archive of UFPA (AC) developed in the context of the extension project “Disseminating archives: Revealing memories and Telling History (phase II)'', of the Faculty of Archivology. Methodologically, this experience was guided by bibliographical and documental research, in addition to field research carried out on the premises of the AC. It is concluded that the collections of the Central Archive, the body responsible for document management at UFPA, in addition to preserving the institutional memory of the university, constitute relevant sources of research for several areas of knowledge. The audiovisual product resulting from the extensionist experience reported in this research, by giving visibility to these collections, contributes to their dissemination, expanding their reach and access to the general public, beyond the academic community.